2007
DOI: 10.1007/s10753-007-9053-z
|View full text |Cite
|
Sign up to set email alerts
|

The Treatment with Antibody of TNF-α Reduces the Inflammation, Necrosis and Fibrosis in the Non-alcoholic Steatohepatitis Induced by Methionine- and Choline-deficient Diet

Abstract: To assess the effects of anti-TNF-alpha antibody (infliximab) in experimental steatohepatitis induced by methionine- and choline-deficient (MCD) diet. The study included thirty rats. One group received normal rat food, and two groups received MCD diet. The treatment group received a single dose intra-peritoneal infliximab (4 mg/kg), at week 8. MCD diet increased levels of AST, ALT, TNF-alpha, TGF-beta(1), tissue and plasma MDA (p < 0.05 for each). Moreover, it led to steatosis, ballooning degeneration, inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
82
1
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(88 citation statements)
references
References 35 publications
3
82
1
2
Order By: Relevance
“…The study by Koca et al also did not report a significant improvement in hepatocyte ballooning, in contrast to our observation of a significant improvement in hepatocyte ballooning in the MCD+infliximab group (27,28).…”
Section: Discussioncontrasting
confidence: 99%
“…The study by Koca et al also did not report a significant improvement in hepatocyte ballooning, in contrast to our observation of a significant improvement in hepatocyte ballooning in the MCD+infliximab group (27,28).…”
Section: Discussioncontrasting
confidence: 99%
“…However, the MCH1R antagonist did not affect MCP-1 levels in the MCD diet-induced model, suggesting that MCP-1 might have a more important role in obese-than in lean steatohepatitis. On the other hand, it is reported that leptin and TNFa are also important factors in the progression of fibrogenesis or inflammation in MCD diet-induced NASH (Sahai et al 2004, Koca et al 2008. In accordance with these reports, we showed that plasma leptin levels and hepatic TNFa mRNAs were significantly reduced in obese and lean NASH models.…”
Section: Discussionsupporting
confidence: 91%
“…For example, the induction of TNF␣ was reduced in low TF mice and PAR-1 Ϫ/Ϫ mice fed the MCD diet. Several studies implicate TNF␣ as a mediator of liver inflammation in mice fed the MCD diet, [45][46][47] although this is not the case for all studies. 9 Similarly, TF and PAR-1 contributed to hepatic expression of COX-2, which has been shown to contribute to hepatic inflammatory cell accumulation in mice fed the MCD diet.…”
Section: Discussionmentioning
confidence: 99%